A Study Correlation between Levels IL-15, IL-23 and TNF-α in a Sample of Iraqi Psoriasis Patients - Amar Sabri, Samara; Ibraheem , Shaima R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Abstract Psoriasis is defined as a series of events that begins in its initial stage with dermatitis and then progresses to more widespread inflammation and increased oxidative stress. The aim of this study was to determine whether psoriasis and the levels of IL-15, IL-23, and TNF-α are related, the ELISA technique was used to detect the levels of inflammation in psoriasis patients and to compare them with healthy individuals. This study included 150 samples, including 90 patients with psoriasis and 60 healthy individuals, and the study was conducted from November 2021 to April 2022. The current study revealed that there was a significant difference in the level of TNF-α in the group of psoriasis patients compared to its level in healthy individuals. Also, there was a significant increase in the level of IL-23 in psoriasis patients compared to its level in the healthy individuals, while there was no significant difference in the level of IL15 between the two groups. However, the statistical study showed a positive and highly significant correlation between IL-15 and IL-23 levels in psoriasis patients, as well as the same relationship between IL-15 and TNF-α levels, in addition to a significant correlation between IL-23 and TNF-α levels in the group of patients. This shows that there is a clear association between these interleukins and psoriasis and its association with the inflammatory status of psoriasis patients, although there was no increase in the level of interleukin-15, the association of interleukin-15 with other inflammatory indicators proves its involvement in psoriasis and an indirect effect on the inflammatory state of psoriasis.